2011
DOI: 10.1016/j.vaccine.2011.07.133
|View full text |Cite
|
Sign up to set email alerts
|

Virus aggregating peptide enhances the cell-mediated response to influenza virus vaccine

Abstract: Given the poor immunogenicity of current H5N1 influenza vaccines, additives and adjuvants remain a viable solution for increasing efficacy. Here, we demonstrate that a 20-amino acid peptide (EB) possessing influenza antiviral activity also enhances the immune response to H5N1 vaccination in mice. The addition of EB to formalin-inactivated whole-virus vaccine induced virion aggregation and these aggregates were readily engulfed by phagocytic cells in vitro. In vivo, mice vaccinated with a suboptimal dose of ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…As such, it is usually taken as a general indicator of the health of the animal, particularly in studies involving influenza virus and other viruses (11,(58)(59)(60). Studies using weight loss as an outcome measure typically do not go beyond the single general measure to parse out the potential mechanisms involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it is usually taken as a general indicator of the health of the animal, particularly in studies involving influenza virus and other viruses (11,(58)(59)(60). Studies using weight loss as an outcome measure typically do not go beyond the single general measure to parse out the potential mechanisms involved.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to neovascularization, animal weight loss is a measure commonly used to gauge the severity of viral infections, including influenza (11). A recent phenotypic trait analysis of HSV-1-induced weight loss identified a region of mouse chromosome 12 associated with maximum weight loss (12).…”
mentioning
confidence: 99%
“…Sera collected from vaccinated mice were treated with a receptor destroying enzyme from Vibrio cholera (Denka-Seiken, San Francisco, CA) before testing for the presence of H5 specific antibodies, as reported previously [40]. Sera were mixed with 4 HA units of inactivated A/Vietnam/1203/2004 vaccine (BEI Resource) and incubated with 0.5% (v/v) chicken red blood cells.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with non-aggregated forms, higher immunogenicity in mice has been observed for aggregates generated under different stress conditions for various TPPs, such as human interferon alpha2b [87][88][89], human mAbs [90][91][92], human epoetin alfa [83], human Factor VIII [93,94], human interferon beta [95], and murine growth hormone [96]. The detailed mechanisms of aggregate-induced immunogenicity are still unknown, but it has been observed that aggregation enhances antigen uptake, increases the total amount of peptides associated with MHC II molecules, and increases danger signals to maturate dendritic cells and activate T cells [52,86,91,97,98]. Therefore, aggregates could contribute to increased immunogenicity through enhancing antigen processing and presentation in the T cell-dependent pathway.…”
Section: Factors That Influence Immunogenicitymentioning
confidence: 99%